Pengaruh Literasi Keuangan Terhadap Kemampuan Pengelolaan Keuangan Mahasiswa Digitech University - Nurinayah, Ghania; Susilawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Students need financial literacy to manage their finances effectively. Education expenditures, everyday requirements, and future planning are common financial issues for students. However, insufficient financial literacy might hinder financial management. money literacy and Digitech University students' money management abilities are examined in this research. This research technique is quantitative with a descriptive approach. Data were obtained through a survey of students of the Management and Accounting Study Program, class of 2021. The research found a favorable association between financial knowledge and student financial management. Most students grasp finance fundamentals, but they lack everyday financial abilities. Higher financial literacy respondents save more, budget better, and handle funds wisely. This research emphasizes the necessity of financial education for students to better their finances. Therefore, colleges should be able to conduct more organized and relevant financial literacy programs.